Reformulasi Pengaturan Legitieme Portie dalam Hukum Waris Perdata Barat untuk Mewujudkan Keadilan Substantif di Indonesia (Studi Kasus Sengketa Waris Keluarga Campuran di Surabaya) - Suci, Vebricia Rahmah; Yunanto, Yunanto (Riwayat: Educational Journal of History and Humanities, 2025)
The incongruity between the concept of legitieme portie in Western civil inheritance law and the principles of substantive justice that have developed within the Indonesian legal system reflects a fundamental need for legal reform. The legitieme portie, as regulated in the Burgerlijk Wetboek (BW), is absolute in nature and emphasizes the inviolable rights of certain heirs without considering social, economic, or moral dimensions. This rigidity often results in substantive injustice and generates conflicts in the distribution of inheritance. This study employs a normative legal research method with statutory, conceptual, and comparative approaches to analyze the regulation of legitieme portie and its relevance within the national legal context. The findings reveal that the application of Western civil inheritance law remains rooted in individualistic values that are incompatible with the principles of kinship and social justice underpinning Indonesias legal philosophy. Therefore, a reformulation of legitieme portie is necessary so that it is no longer understood as an absolute right but as a minimum guarantee for the welfare of weaker heirs, taking into account their contributions and moral responsibilities. By integrating the principles of substantive justice grounded in Pancasila values, Indonesias inheritance law can evolve into a more humanistic, adaptive, and socially just legal system.